Thoracolumbar spine fracture patterns, etiologies, and treatment modalities in Jordan - Ahmad Almigdad; Sattam Alazaydeh; Mohammad Bani Mustafa; Mu'men Alshawish; Anas Al Abdallat (Journal of Trauma and Injury)
Purpose Spine fractures are a significant cause of long-term disability and socioeconomic burden. The incidence of spine fractures tends to increase with age, decreased bone density, and fall risk. In this study, we evaluated thoracolumbar fractures at a tertiary hospital in Jordan regarding their frequency, etiology, patterns, and treatment modalities. Methods The clinical and radiological records of 469 patients with thoracolumbar fracturesadmitted to King Hussein Medical City from July 2018 to August 2022 were evaluated regarding patients’ age, sex, mechanism of injury, fracture level and pattern, and treatment modalities. Results The mean age of patients was 51.24±20.22 years, and men represented 52.7%. Compression injuries accounted for 97.2% of thoracolumbar fractures, and the thoracolumbar junction was the most common fracture location. Falling from the ground level was the most common mechanism and accounted for half of the injuries. Associated neurological injuries were identified in 3.8% of patients and were more common in younger patients. Pathological fractures were found in 12.4% and were more prevalent among elderly patients and women. Conclusions Traffic accidents and falling from height were the most common causes of spine fractures in patients younger than 40. However, 70% of spine fractures in women were caused by simple falls, reflecting the high prevalence of osteoporosis among women and the elderly. Therefore, traffic and work safety measures, as well as home safety measures and osteoporosis treatment for the elderly, should be recommended to reduce the risk of spine fractures.